2021
DOI: 10.1007/s10989-021-10339-0
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico Design of a Novel Tridecapeptide Targeting Spike Protein of SARS-CoV-2 Variants of Concern

Abstract: Several mutations in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have increased the transmission and mortality rate of coronavirus disease-19 (COVID-19) across the globe. Although many vaccines have been developed, a large proportion of the global population remains at high risk of infection. The current study aims to develop an antiviral peptide capable of inhibiting the interaction of SARS-CoV-2 spike protein and its six major variants with the host cell angiotensin-converting enzyme 2 (ACE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The other in silico investigation was aimed to design a peptide‐based inhibitor named Mod13AApi with the potential to interfere with the attachment of spike protein of SARS‐CoV‐2 and its variants to ACE2. In this work, by employing molecular docking experiment, some similar interactions were also predicted for this tridecapeptide in complex with spike protein and its variants like the interactions anticipated for our study [28] . In 2021, Acharya and colleagues reported a study in which two potential compounds (called MU‐UNMC‐1 and MU‐UNMC‐2) as entry inhibitors for SARS‐CoV‐2 and its variants were discovered using virtual screening technique.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…The other in silico investigation was aimed to design a peptide‐based inhibitor named Mod13AApi with the potential to interfere with the attachment of spike protein of SARS‐CoV‐2 and its variants to ACE2. In this work, by employing molecular docking experiment, some similar interactions were also predicted for this tridecapeptide in complex with spike protein and its variants like the interactions anticipated for our study [28] . In 2021, Acharya and colleagues reported a study in which two potential compounds (called MU‐UNMC‐1 and MU‐UNMC‐2) as entry inhibitors for SARS‐CoV‐2 and its variants were discovered using virtual screening technique.…”
Section: Resultssupporting
confidence: 75%
“…In this work, by employing molecular docking experiment, some similar interactions were also predicted for this tridecapeptide in complex with spike protein and its variants like the interactions anticipated for our study. [28] In 2021, Acharya and colleagues reported a study in which two potential compounds (called MU‐UNMC‐1 and MU‐UNMC‐2) as entry inhibitors for SARS‐CoV‐2 and its variants were discovered using virtual screening technique. These molecules were experimentally evaluated in a live SARS‐CoV‐2 infection assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, current research is also focused on developing alternative, smaller molecules capable of interfering with the interaction of the SARS-CoV-2 spike protein with cellular ACE2 [ 12 , 13 , 14 , 15 ]. Over the past two years, a range of studies have reported the computational design of smaller proteins or peptides, either based on the structure of the two N-terminal α-helices of ACE2, through which it contacts the receptor binding domain (RBD) of the SARS-CoV-2 spike protein [ 16 , 17 , 18 , 19 ], or through de novo design based on the RBD structure [ 19 , 20 , 21 ]. In a mechanism similar to antibodies, such peptides and miniproteins can be expected to bind to RBD, preventing its interaction with ACE2, thus blocking infection.…”
Section: Introductionmentioning
confidence: 99%